Experience feedback on operation of low-temperature vacuum evaporation-based desalination plant integrated with CIRUS. (10th September 2008) - Ranjan, Rakesh; Kumar, Surinder; Ramesh, N.; Sharma, R.C.
CIRUS is a 40 MWth, heavy water-moderated, light water-cooled and natural uranium-fuelled research reactor located at Trombay, Mumbai. The reactor has been in operation since 1960 with an average availability factor of about 70% for about three decades. During the early 1990s, the reactor exhibited signs of ageing. It was refurbished and put back into operation at high power in 2003. Bhabha Atomic Research Centre (BARC) has been engaged in R&D activities related to desalination. Using low-temperature vacuum evaporation technology, the centre has been studying the possibility of using the waste heat of nuclear reactors for seawater desalination. Based on this know-how, a 30 cu m per day (30 tonnes/day) pilot plant has been designed. With the aim of demonstrating the utilisation of waste heat from research reactor, it was decided to integrate the unit to CIRUS during refurbishing outage of the reactor. The work involved the design, installation and commissioning of a set-up to transfer heat from the primary coolant of CIRUS to the desalination unit through an intermediate demineralised water circuit. The unit has been operated at its rated capacity and its performance has been satisfactory. The product water has been utilised to augment the demineralised water inventory of the primary coolant system. This paper highlights the experience gained during the installation, commissioning and operation of the desalination unit.